A Systematic Review of Binge Eating, Loss of Control Eating, and Weight Loss in Children and Adolescents - Moustafa, Afaf F. (Obesity (Silver Spring), 2021)
OBJECTIVE: This review synthesizes literature on changes in binge eating (BE) and loss of control eating (LOC) following weight loss, and the association between BE/LOC and weight loss in children and adolescents. METHODS: A systematic literature search was conducted in PubMed, Scopus, and PsycInfo. Eligible studies included all peer-reviewed journal articles of primary research that assessed BE/LOC and weight change following a weight loss intervention in individuals under 18 years of age. RESULTS: The 29 articles included studies on behavioral therapy, pharmacotherapy, and surgical interventions. Four of 14 studies showed that higher baseline BE/LOC was associated with less weight loss, while 10 showed no significant association. BE/LOC behaviors significantly decreased following weight loss interventions in 20 of 21 studies. A greater decrease in BE/LOC was associated with improved weight loss in four of nine studies that assessed this change. CONCLUSIONS: Weight loss interventions are associated with improved BE/LOC in youth with obesity. Persistence of BE/LOC symptoms may be associated with less weight loss. These results can aid in guiding future treatment for youth with BE/LOC seeking weight loss treatment.